Urgensi Pemahaman Sejarah Indonesia dalam Mewujudkan Sikap Bela Negara Mahasiswa Program Studi Pendidikan Sejarah Universitas Jambi - Lisa Rukmana; Yoan Mareta (Universitas Batanghari Jambi, 2023)
This study aims to analyze the relationship between understanding Indonesian history and students' national defense attitudes. This research is a type of quantitative research with a correlational approach. The sample used was 257 students, data collection using questionnaires and tests. Questionnaires are used to reveal data about the attitude of state defense, while tests are used to reveal understanding of Indonesian history. Data analysis techniques using quantitative descriptive analysis. The prerequisite test of analysis is normality test and linearity test. Hypothesis testing using Karl Pearson correlation poduct moment. The results of the findings show that there is a positive and significant relationship between understanding Indonesian history and students' national defense attitudes with a correlation coefficient of 0.742. Thus, if the understanding of Indonesian history is high, it will lead to a strong state defense attitude in students.